Implementation of Enviromental, Social, and Governance (ESG) Principles in Companies as a Strategy to Realize Sustainable Development Goals (SDGS) in Talang Buluh Village, Banyuasin Regency, South Sumatera Province - Serlika Aprita; Heni Marlina; Yonani Yonani; Wulan Purnama Sari; Serli Margareta (Sean Institute, 2026)
The implementation of Environmental, Social, and Governance (ESG) principles in companies has become a new paradigm in sustainable business management in the era of globalization. ESG is no longer just an indicator of corporate ethics, but also a strategic foundation that integrates environmental, social, and governance responsibilities in all aspects of a company's operations. In a legal context, ESG strengthens compliance with environmental, employment, and corporate governance regulations, while supporting the principles of good corporate governance and public accountability. ESG has challenges in implementing high implementation costs, limited resources, in integrating ESG into business strategies. Best practices in implementing ESG are integrating ESG into business strategies, measuring and reporting ESG performance transparently, increasing employee awareness and training regarding economics and business or ESG. The implementation of ESG principles not only strengthens the company's image and reputation but can also help the company improve its business sustainability, reduce risks By understanding the benefits, challenges, and best practices of ESG implementation, companies can create long-term value for their stakeholders, who use it to evaluate company performance and measure overall risk management. The implementation of ESG principles not only strengthens the company's image and reputation but also paves the way for creating an inclusive, ethical, and sustainable development-oriented business ecosystem.